2023
DOI: 10.1055/a-2058-3863
|View full text |Cite
|
Sign up to set email alerts
|

Bio-evaluation of Untapped Alkaloids from Vinca minor Enriched by Methyl-jasmonate-induced Stress: an Integrated Approach

Abstract: The low amount of metabolites isolated from natural products is one of the challenges preventing their biological evaluation. The modulation of biosynthetic pathways by stimulating stress-induced responses in plants, was proven to be a valuable tool for diversification of already known natural products. Recently, we reported the dramatic effect of Methyl jasmonate (MeJA) on Vinca minor alkaloids distribution. In this study, three compounds identified as 9-methoxy vincamine and minovincinine and minovincine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In silico tools such as network pharmacology and molecular docking emerged as a reliable tool for identifying the interaction and correlation between different pathways so that we can gain new insights about unexplored mechanisms of actions of drugs [25]. In…”
Section: Discussionmentioning
confidence: 99%
“…In silico tools such as network pharmacology and molecular docking emerged as a reliable tool for identifying the interaction and correlation between different pathways so that we can gain new insights about unexplored mechanisms of actions of drugs [25]. In…”
Section: Discussionmentioning
confidence: 99%
“…After that, poses are ranked according to their score. 87 Finally, the best pose was visualized to study its interaction with the binding site through the Discovery studio visualizer. 88 4.4.3.…”
Section: Discussionmentioning
confidence: 99%
“…The blind docking approach was utilized to study the interaction of the compounds with identified active sites. After that, poses are ranked according to their score . Finally, the best pose was visualized to study its interaction with the binding site through the Discovery studio visualizer …”
Section: Methodsmentioning
confidence: 99%
“…Template based docking was used to study the ability of the compounds to interact with different detected binding cavities then the software rank the poses according to their score. 79 Finally, the visualization of the best pose was carried out using discovery studio visualizer to study their interaction with the binding site. 80 …”
Section: Methodsmentioning
confidence: 99%